2016
DOI: 10.1089/ars.2016.6695
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Monocyte and Macrophage Function

Abstract: The key challenges in the upcoming years will be to study epigenetic changes in human disease and to better understand how epigenetic pathways control the inflammatory repertoire in disease. Antioxid. Redox Signal. 25, 758-774.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 145 publications
(174 reference statements)
2
69
0
2
Order By: Relevance
“…Overall, we found that stimulation drives dramatic changes in regulatory landscapes of B and T cells. In contrast, we saw limited effects in innate lineage cells ( Figure S3A,B), perhaps because the chromatin response in the innate lineage cells is poised or transient (22,24,25). Figure 2A).…”
Section: Stimulation Results In Large-scale Chromatin and Gene Expresmentioning
confidence: 80%
“…Overall, we found that stimulation drives dramatic changes in regulatory landscapes of B and T cells. In contrast, we saw limited effects in innate lineage cells ( Figure S3A,B), perhaps because the chromatin response in the innate lineage cells is poised or transient (22,24,25). Figure 2A).…”
Section: Stimulation Results In Large-scale Chromatin and Gene Expresmentioning
confidence: 80%
“…Among them, monocyte activation and proliferation are critical steps corresponding to bacterial infection [27]. Mounting evidence shows that epigenetics modulates host innate immunity against exogenous pathogens through multi-channel mechanisms involving in DNA methylation, histone post-translational modification and the activity of non-coding RNAs [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that cells retain the "memory" of this context in culture. Indeed, the concept of epigenetic memory of innate immune cells such as macrophages has been proposed to play an important role in modulating immune responses (48)(49)(50)(51). Although this has been mainly studied in the context of pro-inflammatory stimuli and the regulation of pro-inflammatory gene expression, there are also reports showing a distinct metabolic environment (for instance in type 2 diabetes) can epigenetically imprint bone marrow progenitor cells that can derive into a "pre-programmed macrophage state associated with changes in gene expression (51).…”
Section: Discussionmentioning
confidence: 99%